Applications of LC-QQQ for quantification of small molecules in biological media - Schwarz, Madeline Christine Roach, author; Reynolds, Melissa, advisor; Van Orden, Alan, committee member; Chung, Jean, committee member; VandeWoude, Sue, committee member (Colorado State University. Libraries, 2025)
Liquid chromatography triple quadrupole mass spectrometry (LC-QQQ) is a popular instrumental technique with rising popularity in research and clinical laboratories. LC-QQQ allows for high analytical specificity due to specific biomarker detection, along with high analytical sensitivity due to the trace amounts of substances being accurately quantified. Due to these specific advantages, LC-QQQ is gaining popularity for clinical diagnoses to determine the extent of an infection or disease, leading to better informed treatment, or to determine the metabolic rate at which a drug moves through the body. Small molecules (<1000 Daltons) can be used as biomarkers for both clinical diagnosis and metabolomic studies and are detected at extremely low levels using LC-QQQ. This work endeavors to utilize LC-QQQ for two primary applications: first, for the detection of a biomarker for the purposes of diagnosing pulmonary fungal infections, second, for the detection of cannabinoids in plasma during their metabolism. Pulmonary fungal infections such as invasive pulmonary aspergillosis (IPA) have increased in incidence over the last decade due to the increased number of immunocompromised individuals. This increase is especially problematic when considering mortality rates associated with IPA are upwards of 70%. This mortality rate, in part, is due to the length of time it takes to diagnose a patient with IPA. When diagnosed early, mortality rates of IPA decrease by as much as 30%. Chapter 1 discusses current technologies employed in both medical and research laboratories to diagnose IIPA, including culture, imaging, polymerase chain reaction, peptide nucleic acid-fluorescence in situ hybridization, enzyme-linked immunosorbent assay, lateral flow assay, and liquid chromatography mass spectrometry. For each technique, Chapter 1 discusses both promising results and potential areas for improvement with each technique, paying special attention to liquid chromatography mass spectrometry as a potential diagnostic method. Due to the demonstrated need for diagnostic methods that decrease time-to-diagnosis for IPA, Chapter 2 discusses the development and implementation of a method for the quantification for low levels of glucosamine from Aspergillus species using LC-QQQ. The limit of detection in the final method used on samples of Aspergillus was calculated to be 0.020 ± 0.001, with a limit of quantification of 0.061 ± 0.004 ng/mL. The method described in Chapter 2 also has a high internal repeatability (R2 = 0.9996) and does not require a derivatization step for specificity. This allows for ease of translation to a clinical setting. The method was applied to several pathogenic species of Aspergillus, including Aspergillus fumigatus, which causes more than 90% of cases of IPA. Due to the reduced sample prep and run time, high analytical sensitivity, and high specificity the developed glucosamine detection method discussed in Chapter 2 was applied to samples of biological media relevant to clinical diagnosis of IPA in Chapter 3. Artificial sputum medium and artificial bronchioalveolar lavage fluid were used to determine the matrix effects of clinical samples on the developed method. The FDA's bioanalytical method development standards were applied, and it was determined that the artificial media cause extremely strong and inconsistent matrix effects. Separation methods were also tested to remove the glucosamine from the artificial media but were unsuccessful. These results show that the method requires further validation before it can be implemented on clinical samples. Chapter 4 delves into a method to detect CBD, Δ9-tetrahydrocannabinol, and their major metabolites using LC-QQQ. Cannabinoids and their metabolites are of major interest to the medical community due in part to their recent decriminalization. Chapter 4 details the LC-QQQ method developed, as well as the endeavors to account for matrix effects. Several protein precipitation methods were tested in an attempt to reduce sample preparation time and increase throughput. Unfortunately, the separation methods developed did not lead to quality control samples that met FDA standards, so more work is needed before the method can be applied to clinical samples. While the methods described are not fully realized for clinical sample testing, the research described provides valuable insights into a few areas. First, it is the first work to describe LC-QQQ detection of glucosamine derived from several fungal species. The work also provides insight for future method optimization work. Finally, this work demonstrates the effect that matrices can have on method development and some of the problem-solving steps that are required to bring a method from the research lab to a clinical setting.
Keywords: cannabinoids; LC-QQQ; method development; glucosamine; Aspergillus; mass spectrometry